Luminous Stars in Nearby Galaxies - Humphreys, Roberta M. (MDPI - Multidisciplinary Digital Publishing Institute, 2020)
Studies on the populations of luminous stars in nearby resolved galaxies have revealed a complex distribution in the luminosity-temperature plane (the HR diagram). The fundamentals of massive star evolution are mostly understood, but the roles of mass loss, episodic mass loss, rotation, and binarity are still in question. Moreover, the final stages of these stars of different masses and their possible relation to each other are not understood. The purpose of this volume is to provide a current review of the different populations of evolved massive stars. The emphasis is on massive stars in the Local Group, the Magellanic Clouds, and the nearby spirals M31 and M33.